Hematological reference values for Alouatta palliata (Primates: Atelidae) and Cebus imitator (Primates: Cebidae) from the Pacific Coast of Costa Rica - Chaves Ramírez, Andrea; Nuñez Vega, Genuar; Arguedas Porras, Randall; Bonilla Vargas, José; Silva de la Fuente, Sandra; Arias-Echandi, María; Gutiérrez-Espeleta, Gustavo (Revista de Biología Tropical, 2022)
Introduction: Wildlife hematological patterns are fundamental for health monitoring, and allows elucidating variations both within and between populations. Among these, hematological parameters are particularly valuable to evaluate the health status of neotropical primate species in the wild. Objective: To define hematological reference values for two species of monkeys in Costa Rica. Methods: During 2014, we collected blood samples from free-ranging mantled howler monkeys, Alouatta palliata (17 females, 18 males) and white-faced capuchin monkeys, Cebus imitator (5 females, 7 males) in seven localities of the Costa Rican Pacific coast. Results: For both species, the hematological values were higher in males, and howler monkey populations differed significantly except for platelets. Conclusions: These hematological values, which differ by sex and locality, will help evaluate the health status of these neotropical primate populations.